METHOD FOR SURFACE TREATMENT OF Ti AND Al UNDER THE SAME CONDITION FOR ADHESIVE BONDING BETWEEN POLYMER AND METAL

JP2025035492AActive Publication Date: 2025-03-13GEO NATION CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023142556
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-13
Estimated Expiration
2043-09-01

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、種類が全く異なる金属であるTiとAlを同一条件で表面処理を行い、表面に多孔性酸化被膜を形成して、それぞれのTiとAlのポリマー間の接合力を測定した結果、引張力、熱衝撃後引張力、恒温恒湿後引張力でTiとAlのそれぞれを表面処理した結果と同一又は優秀な接合力を有する効果を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035492000001_ABST
    Figure 2025035492000001_ABST
Patent Text Reader

Abstract

To provide a method for surface treatment of Ti and Al, which are completely different types of metals, under the same conditions to form a porous oxide film on the surface.SOLUTION: A method for surface treatment of metals under the same conditions for adhesive bonding between a polymer and the metal by a combination of a polymer and Ti or a combination of a polymer and Al includes: a degreasing treatment step in which contaminants are removed from the surface of the metal using a degreasing detergent; a primary etching treatment step in which the surface of the metal is etched using an alkaline solution; a desmuting treatment step in which smut is removed from the surface of the metal; an activation treatment step in which the surface of the metal is etched using a strongly acidic solution; an oxidation anodizing treatment step in which porosity is formed on the surface of the activated metal; and a drying step in which the surface of the anodized metal is dried.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for surface treatment of metals under the same conditions for adhesive bonding of polymers and metals, and more particularly to a method for surface treatment of Ti and Al, which are completely different metals, under the same treatment conditions to form a porous oxide film on the surface. [Background technology]

[0002] Polymer-Ti bonded bodies and polymer-Al bonded bodies are often used in electronic parts and smartphones that require waterproofing, but because the conditions for the surface treatment processes of Ti and Al are different, they cannot be worked on simultaneously, and the conditions for the processes of Ti (Patent Document 1) and Al (Patent Document 2) must be changed each time, which creates problems in terms of time and cost. Especially when the number of parts is small, there is a lot of waste of time and cost. In order to solve the above problems, we developed a method to treat Ti and Al under the same conditions, with each surface treatment condition (solution, concentration, temperature, time, current, etc.) set to a single set. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-048407 A [Patent Document 2] Patent No. 4600701 Summary of the Invention [Problem to be solved by the invention]

[0004] The object of the present invention is to provide a method for solving the above-mentioned problems by performing surface treatment under the same conditions on Ti and Al, which are completely different metals, to form a porous oxide film on the surface. [Means for solving the problem]

[0005] The surface treatment method of metal under the same conditions for adhesive bonding of polymer and metal by the combination of polymer and Ti or polymer and Al of the present invention is as follows: a degreasing step of removing contaminants from the surface of the metal using a degreasing detergent; a first etching step of etching the surface of the metal using an alkaline solution; a desmutting step for removing smut from the surface of the metal; an activation step of etching the surface of the metal using a strong acid solution; an oxidative anodizing step for forming porosity on the surface of the activated metal; and and drying the anodized surface of the metal.

[0006] In the oxidation anodizing step, A mixed acid solution containing at least one of sulfuric acid: concentration 1-3 g / L, phosphoric acid: concentration 2-7 g / L, chromic acid: concentration 1-5 g / L, oxalic acid: concentration 1-5 g / L, and hydrofluoric acid: concentration 0.5-2 g / L, and at least one of sodium sulfate: concentration 5-10 g / L, phosphate: concentration 1-5 g / L, and oxalate: concentration 1-3 g / L, pH 4.5-5.5, and a silane coupling agent: concentration 0.01-0.10 g / L as an additive, is added, and the current is 1.0-2.5 A / dm at 30-50°C. 2 The anodizing treatment is performed at a current density of 100 to 2000 for 300 to 900 seconds.

[0007] In the oxidation anodizing step, the additive, the silane coupling agent, 1,3,5-triazine-2,4,6-trithiol (TT), 1,3,5-triazine-2,4,6-trithiol monosodium (TTN), 1,3,5-triazine-2,4,6-trithioltriethanolamine (F-TEA), 6-anilino-1,3,5-triazine-2,4-dithiol (AF), 6-anilino-1,3,5-triazine-2,4-dithiolumo sodium (AFN), 6-dibutylamino-1,3,5-triazine-2,4-dithiol (DB), 6-Dibutylamino-1,3,5-triazine-2,4-dithiol monosodium (DBN), 6-diallylamino-1,3,5-triazine-2,4-dithiol (DA), 6-Diallylamino-1,3,5-triazine-2,4-dithiol monosodium (DAN), 1,3,5-triazine-2,4,6-trithiol di(tetrabutylammonium salt) (F2A), 6-dibutylamino-1,3,5-triazine-2,4-dithiol tetrabutylammonium salt (DBA), 6-dioctyl-1,3,5-triazine-2,4-dithiol (DO), 6-Dioctyl-1,3,5-triazine-2,4-dithiol monosodium (DON), 6-dilaurylamino-1,3,5-triazine-2,4-dithiol (DL), 6-Dilaurylamino-1,3,5-triazine-2,4-dithiol monosodium (DLN), 6-stearylamino-1,3,5-triazine-2,4-dithiol (ST), 6-stearylamino-1,3,5-triazine-2,4-dithiol monopotassium (STK), 6-oleylamino-1,3,5-triazine-2,4-dithiol (DL), and The present invention is characterized by using one of the triazine thiol derivatives of 6-oleylamino-1,3,5-triazine-2,4-dithiol monopotassium (OLK) and their salts. Effect of the Invention

[0008] According to the present invention, Ti and Al, which are completely different metals, are surface-treated under the same conditions, a porous oxide film is formed on the surface, and the adhesive strength between the polymer of each Ti and Al is measured. As a result, it is possible to obtain the same or superior adhesive strength as the results of surface-treating Ti and Al individually in terms of tensile strength, tensile strength after thermal shock, and tensile strength after constant temperature and humidity. [Brief description of the drawings]

[0009] [Figure 1] 1 is a flow chart showing a method for surface treatment of metal under the same conditions for adhesive bonding of polymer and metal by combination of polymer and Ti or polymer and Al. [Diagram 2] (a) is a plan view showing the shape of a Ti or Al metal member of a tensile test specimen, (b) is a side view showing the shape of a Ti or Al metal member of a tensile test specimen, and (c) is a diagram explaining a metal bonded body between a Ti or Al metal member of a tensile test specimen and a polymer. A polymer is injected from a gate and bonded to the Ti or Al metal member. [Diagram 3] (a) is a photograph (magnification: 105 times) of the surface shape of a porous oxide film of Ti suitable for the surface treatment according to the present invention, and (b) is a photograph (magnification: 105 times) of the surface shape of a porous oxide film of Al suitable for the surface treatment according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] A method for surface treatment of metal under the same conditions for adhesive bonding of polymer and metal according to the present invention shown in FIG. 1 will now be described. According to one embodiment of the present invention, a method for surface treatment of a metal under the same conditions for adhesive bonding of a polymer and a metal by a combination of a polymer and Ti or a polymer and Al is as follows: (a) a degreasing step for removing contaminants from the surface of a metal using a degreasing detergent; (b) a water washing step in which the metal surface is washed with water after the degreasing step; (c) a first etching step of etching the surface of the metal using an alkaline solution; (d) a water washing step for washing the surface of the metal that has been subjected to the first etching process with water; (e) a desmutting step for removing smut from the surface of the metal; (f) a water rinsing step in which the surface of the desmutted metal is washed with water; (g) an activation step in which the surface of the metal is secondarily etched using a strong acid solution; (h) a water rinsing step for rinsing the surface of the activated metal with water; (i) an oxidative anodizing step for forming porosity on the surface of the activated metal; (j) a rinsing step for cleaning the anodized metal surface with water; and (k) a drying step for removing moisture from the surface of the metal washed with water.

[0011] In step (a), contamination of the metal surface is removed by washing with an aluminum degreasing detergent or by immersing in a water-soluble organic solvent at 60° C. for 3 minutes.

[0012] Step (b) is a water washing step in which the metal surface is washed with water to remove the water-soluble organic solvent.

[0013] In step (c), the metal surface is etched with an alkali metal etchant such as KOH, hydroxides of alkali metals, or soda ash (Na2CO3, anhydrous sodium carbonate) containing these, ammonia, etc. at 40°C for 2 minutes to form etching marks on the metal surface and roughen the surface.

[0014] In step (d), the surface of the metal that has been subjected to the first etching is washed with water to remove the alkaline solution from the metal surface.

[0015] In step (e), smut is removed from the metal surface using a smut remover containing nitric acid, sulfuric acid, hydrofluoric acid, ammonium fluoride, sodium fluoride, hydrogen peroxide, or the like at 25°C for 1 minute.

[0016] In step (f), the desmutted metal surface is washed with water to remove the desmutting agent.

[0017] In step (g), the metal surface is subjected to a secondary etching activation treatment in a strong acid solution such as sulfuric acid, acetic acid, organic acid, or fluoric acid at 40°C for 30 seconds.

[0018] In step (h), the activated metal surface is washed with water.

[0019] In the (i) step, a mixed acid solution containing at least one of sulfuric acid: concentration 1-3 g / L, phosphoric acid: concentration 2-7 g / L, chromic acid: concentration 1-5 g / L, oxalic acid: concentration 1-5 g / L, and hydrofluoric acid: concentration 0.5-2 g / L, and at least one of sodium sulfate: concentration 5-10 g / L, phosphate: concentration 1-5 g / L, and oxalate: concentration 1-3 g / L, pH 4.5-5.5 is used, and a silane coupling agent: concentration 0.01-0.10 g / L is added as an additive, and the mixture is subjected to a current flow rate of 1.0-2.5 A / dm at 30-50°C. 2 By performing anodizing treatment at a current density of 10000 for 300 to 900 seconds, an oxide film with many pores is formed on the etched metal surface, and the silane coupling agent penetrates into the pores along with the formed porous pores, thereby increasing the bonding strength between the metal and the polymer and improving the bonding.

[0020] In the step (i), the silane coupling agent, which is an additive, 1,3,5-triazine-2,4,6-trithiol (TT), 1,3,5-triazine-2,4,6-trithiol monosodium (TTN), 1,3,5-triazine-2,4,6-trithioltriethanolamine (F-TEA), 6-anilino-1,3,5-triazine-2,4-dithiol (AF), 6-anilino-1,3,5-triazine-2,4-dithiolumo sodium (AFN), 6-dibutylamino-1,3,5-triazine-2,4-dithiol (DB), 6-Dibutylamino-1,3,5-triazine-2,4-dithiol monosodium (DBN), 6-diallylamino-1,3,5-triazine-2,4-dithiol (DA), 6-Diallylamino-1,3,5-triazine-2,4-dithiol monosodium (DAN), 1,3,5-triazine-2,4,6-trithiol di(tetrabutylammonium salt) (F2A), 6-dibutylamino-1,3,5-triazine-2,4-dithiol tetrabutylammonium salt (DBA), 6-dioctyl-1,3,5-triazine-2,4-dithiol (DO), 6-Dioctyl-1,3,5-triazine-2,4-dithiol monosodium (DON), 6-dilaurylamino-1,3,5-triazine-2,4-dithiol (DL), 6-Dilaurylamino-1,3,5-triazine-2,4-dithiol monosodium (DLN), 6-stearylamino-1,3,5-triazine-2,4-dithiol (ST), 6-stearylamino-1,3,5-triazine-2,4-dithiol monopotassium (STK), 6-oleylamino-1,3,5-triazine-2,4-dithiol (DL), and The triazine thiol derivatives 6-oleylamino-1,3,5-triazine-2,4-dithiol monopotassium (OLK) and one of their salts are used.

[0021] Step (j) is a water rinsing step in which the anodized metal surface is washed with water at 60° C. for 30 seconds.

[0022] The metal surface cleaned in step (k) is dried with hot air at 80° C. for 5 minutes.

[0023] The polymer that can be used in the present invention is a thermoplastic resin, and various polymer resins can be used, including, but not limited to, polybutylene terephthalate (PBT), polyphenylene sulfide (PPS), polyphthalamide (PPA), polyethylene terephthalate (PET), polycarbonate (PC), polyimide (PI), polyaryletherketone (PAEK), polyether-ether-ketone (PEEK), etc. The polymer specimen used in the experiment was polybutylene terephthalate (PBT), WF008NXQ 7N1A4352 from SABIC.

[0024] The surface treatment for manufacturing a joint between a polymer and Ti or Al is compared between the conventional example and the present invention. Table 1 below summarizes the conventional example 1 for Ti, Table 2 summarizes the conventional example 2 for Al, and Table 3 summarizes the surface treatment steps of the present invention.

[0025] [Table 1]

[0026] In the conventional example 1 of Ti in Table 1, in the oxidation anodizing treatment step of step sequence 7, a sulfuric acid solution with a concentration of 180 g / L was used, and a silane coupling agent, 1,3,5-triazine-2,4,6-trithiol with a concentration of 0.01 to 0.10 g / L, was added, and the anodizing treatment was performed at 60° C. with a current of 0.55 A / dm 2 The plate is anodized for 900 seconds at a current density of 1000 .mu.m.

[0027] [Table 2]

[0028] In the conventional example 2 of Al in Table 2, in the oxidation anodizing treatment step of process sequence 7, a mixed alkaline solution of caustic soda (concentration 30 g / L), sodium phosphate (concentration 3 g / L) and phosphoric acid (concentration 10 g / L) was used, and a silane coupling agent, 1,3,5-triazine-2,4,6-trithiol (concentration 0.01 to 0.10 g / L), was added, and the anodizing treatment was performed at 50°C and 5.0 A / dm 2 The plate is anodized for 900 seconds at a current density of 1000 .mu.m.

[0029] [Table 3]

[0030] In the embodiment of the invention in Table 3, in the oxidation anodizing treatment step of step 9, a mixed acidic solution (pH 4-6) of sulfuric acid (concentration 1-30 g / L) and sodium sulfate (concentration 5-15 g / L) was used, and 1,3,5-triazine-2,4,6-trithiol (concentration 0.01-0.10 g / L) was added as a silane coupling agent, and the anodizing treatment was performed at 30-50° C. with 1.0-2.5 A / dm 2 The anodizing process is performed for 300 to 1200 seconds at a current density of 1000.

[0031] In this manner, specimens of Conventional Examples 1 to 2, Invention Examples 1 to 15, and Comparative Examples 1 to 7 were produced under the conditions shown in the table below.

[0032] [Table 4] TIFF2025035492000006.tif38162 (Here, ST is an abbreviation for "standard," meaning "conventional conditions.")

[0033] FIG. 2(a) is a plan view of the metal members of the specimens used in Conventional Examples 1-2, Invention Examples 1-15, and Comparative Examples 1-7, which were manufactured for tensile tests. The specimens were manufactured from Ti (Grade 5) or Al (Al 6061) with dimensions of 12 mm wide, 40 mm long, and 3 mm thick. FIG. 2(c) shows the Ti (Grade 5) or Al (Al 6061) specimens to which a polymer was bonded. A polymer measuring 12 mm wide, 42 mm long, and 3 mm thick was injected vertically from the gate to bond to the Ti or Al.

[0034] The polymer-Ti or Al metal bonded body 3 in FIG. 2(c) is formed by integrally molding a polymer member 2 onto a Ti or Al metal member 1 by injection molding. In injection molding, the Ti or Al metal member 1 is loaded into a mold, and a polymer (thermoplastic resin) is pressed into the joining area to integrally mold the Ti or Al metal member 1 and the polymer member 2. Polybutylene terephthalate (PBT) and polyphenylene sulfide (PPS) can be used as the thermoplastic resin. The contact area between the Ti or Al metal member 1 and the polymer member 2 is approximately 36 mm because they are joined in a straight line. 2 (=12 mm×3 mm). The polymer-Ti or Al metal bonded body 3 in FIG. 2(c) is used as a test piece for a tensile test to examine the bonding strength.

[0035] FIG. 3 shows images of (a) the surface morphology of a porous oxide coating of Ti and (b) the surface morphology of a porous oxide coating of Al, which are suitable for the surface treatment according to the present invention. It can be seen that an oxide film with many pores has formed on the metal surface.

[0036] [Experimental Example 1] <Tensile force experiment> Testing machine: MMS HZ-1003A Testing Method: 1) Prepare a specimen for tensile testing. 2) Attach the test piece to the tensile strength testing jig. 3) Tensile force test at a speed of 5mm / min. 4) The value at the point when the injected polymer and metal peel off is recorded.

[0037] [Experimental Example 2] <Tensile strength experiment after thermal shock> Testing machine: SUKSAN SE-TS-05 Test Method: 1) Place the test specimen in the low temperature room. 2) Test condition setting: Pattern setting temperature [-40~80℃] / 30min / 150 times repeated. 3) After thermal shock test, sample tensile and leak tests were performed.

[0038] [Experimental Example 3] <Tensile strength test after constant temperature and humidity> Testing machine: SUKSAN SE-CT-02 Test Method: 1) Place the sample in a high temperature and humidity storage room. 2) Test condition setting: (Pattern setting temperature [80℃] / humidity [95%] / time [200hr]. 3) After thermal shock test, sample tensile and leak tests were performed.

[0039] Tensile tests, bond strength measurements as a function of time left standing, and sealing tests were carried out on the test pieces of Conventional Examples 1 to 2, Inventive Examples 1 to 15, and Comparative Examples 1 to 7. The results are summarized in Table 5 below.

[0040] [Table 5]

[0041] The test results in the examples are as follows: In Example 1, both the Ti and Al specimens obtained excellent results. In Comparative Example 1, the Ti specimen had poor tensile strength, while the Al specimen had good results. In Example 2, the Ti specimen had good tensile strength, and the Al specimen had excellent results. In Example 3, the Ti specimen had excellent tensile strength, and the Al specimen had good results. In Example 4, both the Ti and Al specimens obtained good results. In Comparative Example 2, the Ti specimen had poor tensile strength, while the Al specimen had good results. In Comparative Example 3, the Ti specimen had a slightly inferior tensile strength, while the Al specimen had a good result. In Comparative Example 4, the Ti specimen had a good tensile strength, while the Al specimen had a slightly inferior result. In Comparative Example 5, the Ti specimen had a good tensile strength, while the Al specimen had an inferior result. In Comparative Example 6, the Ti specimen had a slightly inferior tensile strength, while the Al specimen had a good result. In Example 5, both the Ti and Al specimens obtained good results. In Example 6, both the Ti and Al specimens obtained good results. In Comparative Example 7, the Ti specimen had poor tensile strength, while the Al specimen had good results. In Example 7, both the Ti and Al specimens obtained good results. In Example 8, both the Ti and Al specimens obtained excellent results. In Example 9, both the Ti and Al specimens obtained excellent results. In Example 10, the Ti specimen had excellent tensile strength, and the Al specimen had good results. In Example 11, both the Ti and Al specimens obtained good results. In Example 12, both the Ti and Al specimens obtained good results. In Example 13, both the Ti and Al specimens obtained good results. In Example 14, both the Ti and Al specimens obtained good results. In Example 15, both the Ti and Al specimens obtained excellent results.

[0042] The test results for the conventional example are as follows. In Conventional Example 1, the Ti specimen had poor tensile strength, while the Al specimen had good results. In Conventional Example 2, the Ti specimen obtained good results in terms of tensile strength, while the Al specimen obtained poor results.

[0043] The test results of the Al specimens manufactured under the conditions exclusively for Al as in the conventional example 1 and the Al and Ti specimens manufactured under the respective conditions of the inventive example were equal or excellent. In addition, the test results of the Ti specimens manufactured under the Ti-only conditions as in Conventional Example 2 and the Ti and Al specimens manufactured under the respective conditions of the inventive example were equal or excellent. [Industrial Applicability]

[0044] The present invention is a method for manufacturing a joint between a polymer and Ti or Al, and has the effect of strengthening the bonding strength between the polymer and Ti or Al through surface treatment of Ti or Al under the same conditions, thereby improving the sealing performance of the parts. [Explanation of symbols]

[0045] 1. Ti or Al metal parts 2. Polymer materials 3 Polymer-Ti or Al metal joint 10 holes 20 Injection Gate

Claims

1. A method for surface treatment of metal under the same conditions for adhesive bonding of polymer and metal by a combination of polymer and Ti or polymer and Al, comprising the steps of: a degreasing step of removing contaminants from the surface of the metal using a degreasing detergent; a first etching step of etching the surface of the metal using an alkaline solution; a desmutting step for removing smut from the surface of the metal; an activation treatment step of secondary etching the surface of the metal using a strong acid solution; an oxidative anodizing step for forming porosity on the surface of the activated metal; 2. A method for uniform surface treatment of metals for adhesive bonding of polymers to metals, comprising a step of drying the anodized surface of said metal.

2. In the oxidation anodizing step, A mixed acid solution containing at least one of sulfuric acid: concentration 1-3 g / L, phosphoric acid: concentration 2-7 g / L, chromic acid: concentration 1-5 g / L, oxalic acid: concentration 1-5 g / L, and hydrofluoric acid: concentration 0.5-2 g / L, and at least one of sodium sulfate: concentration 5-10 g / L, phosphate: concentration 1-5 g / L, and oxalate: concentration 1-3 g / L, pH 4.5-5.5, and a silane coupling agent: concentration 0.01-0.10 g / L as an additive, was added, and the resulting solution had a current density of 1.0-2.55 A / dm at 30-50° C. 2 2. The method for surface treatment of metal under uniform conditions for adhesive bonding between a polymer and a metal according to claim 1, wherein the anodizing treatment is performed at a current density of 1000 to 1,2000 s.

3. In the oxidation anodizing step, the additive, the silane coupling agent, 1,3,5-triazine-2,4,6-trithiol (TT), 1,3,5-triazine-2,4,6-trithiol monosodium (TTN), 1,3,5-triazine-2,4,6-trithioltriethanolamine (F-TEA), 6-anilino-1,3,5-triazine-2,4-dithiol (AF), 6-anilino-1,3,5-triazine-2,4-dithiolmonosodium (AFN), 6-dibutylamino-1,3,5-triazine-2,4-dithiol (DB), 6-dibutylamino-1,3,5-triazine-2,4-dithiol monosodium (DBN), 6-diallylamino-1,3,5-triazine-2,4-dithiol (DA), 6-diallylamino-1,3,5-triazine-2,4-dithiol monosodium (DAN), 1,3,5-triazine-2,4,6-trithiol di(tetrabutylammonium salt) (F2A), 6-dibutylamino-1,3,5-triazine-2,4-dithiol tetrabutylammonium salt (DBA), 6-dioctyl-1,3,5-triazine-2,4-dithiol (DO), 6-dioctyl-1,3,5-triazine-2,4-dithiol monosodium (DON), 6-dilaurylamino-1,3,5-triazine-2,4-dithiol (DL), 6-dilaurylamino-1,3,5-triazine-2,4-dithiol monosodium (DLN), 6-stearylamino-1,3,5-triazine-2,4-dithiol (ST), 6-stearylamino-1,3,5-triazine-2,4-dithiol monopotassium (STK), 6-oleylamino-1,3,5-triazine-2,4-dithiol (DL), and The method for surface treatment of metal under the same conditions for adhesive bonding of polymer and metal according to claim 2, characterized in that a triazine thiol derivative of 6-oleylamino-1,3,5-triazine-2,4-dithiol monopotassium (OLK) and one of its salts are used.

Citation Information

Patent Citations

  • Treatment method of titanium-aluminum composite part, preparation method of combination of titanium-aluminum composite part and resin and product

    CN114606560A

  • Composite material composed of aluminum and titanium and its production

    JP1988143291A

  • Electrolytic treatment of titanium and titanium alloy

    JP1991197696A

  • Alumite member, manufacturing method of alumite member and treatment agent

    JP2015232155A

  • Housing of electronic device with different bonded metals and method of manufacturing the same

    US20220418135A1